Georeferencing Sunda pangolin Manis javanica records in Singapore - Muhammad Khairuldin Aziz; Anthony O'Dempsey; Bee Choo Ng; Kalai Vanan Balakrishnan; Sonja Luz; Charlene Yeong; Sharon Chan; Marcus A.H. Chua (Oryx)
In Singapore, the Critically Endangered Sunda pangolin Manis javanica is threatened by habitat loss and fragmentation, and road traffic collisions. To mitigate these threats, an understanding of its spatiotemporal distribution is needed, as identified in the National Conservation Strategy and Action Plan for the species. However, Sunda pangolin occurrence data are held in multiple separate databases, are typically collected using non-standardized methods, and often lack accurate location details. To compile a complete georeferenced database of Sunda pangolin records in Singapore, we consolidated occurrence data from heterogeneous databases and mainstream and social media, and converted locality descriptions into geographical coordinates. We demonstrate the use of this database to analyse data on rescued pangolins and those killed on roads, to aid conservation efforts in Singapore, and describe other potential applications. We georeferenced 482 records of pangolin sightings, rescues and roadkill for 1996–2021, finding an increase in all three over the study period. Roadkill and rescues occurred mostly in central and western Singapore, close to forested areas, and were predominantly of subadults and adult males. The data can be used to inform threat mitigation strategies, post-rescue release plans and further research. The database has already been used in practice, contributing to environmental impact assessments and conservation recommendations. Overall, this georeferenced database demonstrates the value of citizen science and collating wildlife data from multiple sources, and the methods used can be applied to other taxa to aid conservation strategies.